Meggs' history of graphic design - Meggs, Philip B.; Purvis, Alston W. 1943- (Hoboken, N.J. John Wiley & Sons, 2016)
"Meggs' history of graphic design pioneered the coupling of the words "graphic design" and "history by developing and original narrative tracing the progression of a field originating with the development of writing and heading into the digital age. That was in 1983, and now this sixth edition continues the gold-standard tradition of authoritative coverage for designers in the digital age." -- Provided by publisher
Part 1 The prologue to graphic design -- The invention of writing -- Alphabets -- The Asian contribution -- Illuminated manuscripts -- Part 2 A graphic Renaissance -- Printing comes to Europe -- The German illustrated book -- Renaissance graphic design -- An epoch of typographic genius -- Part 3 The bridge to the twentieth century -- Graphic design and the industrial revolution -- The arts and crafts movement and its heritage -- Art nouveau -- The genesis of twentieth-century design -- Part 3 The modernist era -- The influence of modern art -- Pictorial modernism -- A new language of form -- The bauhaus and the new typography -- The modern movement in America -- Part 5 The age of information -- The international typographic style -- The New York school -- Corporate identity and visual systems -- The conceptual image -- Postmodern design -- National visions within a global dialogue -- The digital revolution--and beyond
This book is printed on acid-free paper.
Includes bibliographical references (pages 623-655) and index.
Keywords: Graphic design (Typography) -- History; Book design -- History